2020
DOI: 10.18632/aging.103093
|View full text |Cite
|
Sign up to set email alerts
|

Age-related shifts in gut microbiota contribute to cognitive decline in aged rats

Abstract: Cognitive function declines during the aging process, meanwhile, gut microbiota of the elderly changed significantly. Although previous studies have reported the effect of gut microbiota on learning and memory, all the reports were based on various artificial interventions to change the gut microbiota without involvement of aging biological characteristics. Here, we investigated the effect of aged gut microbiota on cognitive function by using fecal microbiota transplantation (FMT) from aged to young rats. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 41 publications
2
67
0
Order By: Relevance
“…At the phylum level, FMT decreased the relative abundance of Bacteroidetes , while increasing the relative abundance of Actinobacteria . At the genus level, FMT rats showed lower levels of Prevotella , Bacteroides , Parabacteroides , and higher levels of Sutterella ( Li et al, 2020 ).…”
Section: Hippocampal Neurochemicals and Neuroplasticity Are Regulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…At the phylum level, FMT decreased the relative abundance of Bacteroidetes , while increasing the relative abundance of Actinobacteria . At the genus level, FMT rats showed lower levels of Prevotella , Bacteroides , Parabacteroides , and higher levels of Sutterella ( Li et al, 2020 ).…”
Section: Hippocampal Neurochemicals and Neuroplasticity Are Regulatedmentioning
confidence: 99%
“…These results strongly demonstrated that gut microbiota disturbance could induce hippocampal inflammation and memory impairment. Moreover, it has been reported that when FMT is conducted, young recipient rats show impairment in cognitive behavior but an increase in expression of proinflammatory AGEs and their receptor, accompanied by changes in gut microbiota composition ( Li et al, 2020 ). Specifically, Lactobacillus plantarum decreased the expression of hippocampal TLR4 ( Mohammed et al, 2020 ).…”
Section: Gut Microbiota and Hippocampal Inflammationmentioning
confidence: 99%
“…Similarly, fecal transplant gavages from old mice (but not young mice) to germ free mice showed decreased fecal SCFAs production, and recipient animals demonstrated depressive-like behavior, impaired short-term memory, and spatial memory suggesting that aged microbiome alone is sufficient to decrease SCFAs in the host and to produce cognitive decline (Lee et al, 2020). Similarly, fecal microbiota transplantation from old to young rats impaired cognitive behavior, decreased regional homogeneity, changed synaptic structures, increased glycation-end products and enhanced oxidative and inflammatory stress in recipient young animals (Li et al, 2020b). A single-center clinical trial recommended fecal microbiota transplantation as a home therapy which could clinically benefit recovery in elderly patients with Clostridium infection (Jørgensen et al, 2020).…”
Section: Gut Microbiota In Aging and Associated Diseasesmentioning
confidence: 98%
“…Because the intestinal microbiota composition changes along with aging [22,23], relationships between the intestinal microbiota and immunosenescence along with aging have been suggested [24]. In addition, studies using germ-free animal models showed that altered intestinal microbiota along with aging induces increased intestinal permeability, systemic inflammation, and decreased cognitive function [25,26]. Thus, it has been considered that compositional changes in the intestinal microbiota associates with the increase of disease risk along with aging.…”
Section: Introductionmentioning
confidence: 99%